2011
DOI: 10.4236/gsc.2011.13014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cellulose Decomposition by Microwave Plasma and Radio Frequency Plasma

Abstract: Biomass conversion by plasma has the advantage of mainly producing gaseous products, H2, CO and CO2. Though the thermal plasma has been used for this conversion, the plasma temperature is too high to be unfit for the conversion biomass. The temperature of cold plasma, however, is lower under 3000 K. It expects to be adequate for biomass conversion. Cold plasma can be obtained with irradiation microwave (2.45 GHz) or radio frequency (13.5 MHz) under reduce gas pressure. Therefore, in present study, the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The origins of internal stresses may be often attributed to strain mismatch due to thermal heating under plasma or artificial stretching and release or simply a property mismatch. In the present case, we believe that the elevated electron temperatures (flash temperatures) induced by plasma may generally contribute to the surface activation of cellulose, but the effects are smaller on highly crystalline CNWs that are thermally stable up to 200 °C. , Moreover, the eventual high-temperature fraction in low-pressure glow discharge plasma remains small (<1%), but the ion temperatures in the bulk of the cold plasma remain close to room temperature because we used a minimum power of 20 W. It seems that the time for temperature flashes is too short (<1 s) for thermal gradients within the deposited film and the substrate to induce a patterned film morphology over a longer period of time. Also, artificial heating of the nanocomposite film above the glass-transition temperature of the polymer did not remove the buckling pattern due to the reinforcing action of the CNWs.…”
Section: Discussionmentioning
confidence: 70%
“…The origins of internal stresses may be often attributed to strain mismatch due to thermal heating under plasma or artificial stretching and release or simply a property mismatch. In the present case, we believe that the elevated electron temperatures (flash temperatures) induced by plasma may generally contribute to the surface activation of cellulose, but the effects are smaller on highly crystalline CNWs that are thermally stable up to 200 °C. , Moreover, the eventual high-temperature fraction in low-pressure glow discharge plasma remains small (<1%), but the ion temperatures in the bulk of the cold plasma remain close to room temperature because we used a minimum power of 20 W. It seems that the time for temperature flashes is too short (<1 s) for thermal gradients within the deposited film and the substrate to induce a patterned film morphology over a longer period of time. Also, artificial heating of the nanocomposite film above the glass-transition temperature of the polymer did not remove the buckling pattern due to the reinforcing action of the CNWs.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, Konno et al 207 compared the decomposition of cellulose by MW (2.45 GHz) and RF plasma (13.56 MHz) in an Ar plasma. They concluded that the cellulose conversion and syngas amount in the MW plasma was higher than that in RF that produced other gases.…”
Section: High and Very High-temperature Biomass Conversionmentioning
confidence: 99%
“…A comparison of cellulose decomposition by microwave and RF plasma at reduced pressures was fulfilled in [257]. Results suggest that microwave plasma is suitable for cellulose gasification in comparison with RF plasma, since the former highly convert the element of C, H and O to H2 and CO by the higher energy of microwave frequency than that of radio frequency.…”
Section: Plasma Chemical Activity Of Microwave Plasmamentioning
confidence: 99%